Notoginsenoside R1 Promotes Proliferation and Osteogenic Differentiation of hPDLSCs via Wnt/β-Catenin Signaling Pathway - Han R; Zhang W; Zhang L; Zou J; Yang Y; Li H; Zhang J (Dove Medical Press, 2022)
Ruiqi Han,1 Wenjuan Zhang,2 Lina Zhang,3 Jinghua Zou,1 Yanran Yang,1 Hongkun Li,1 Jun Zhang1 1Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Orthodontics, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 3Department of Orthodontics, Faculty of Stomatology, Liaocheng People's Hospital, Liaocheng, People's Republic of ChinaCorrespondence: Jun Zhang, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, No. 44-1 Wenhua Road West, Jinan, 250012, Tel +86 13953109816, Email zhangj@sdu.edu.cnPurpose: To investigate the roles of Notoginsenoside R1 (NG-R1) on the proliferation and osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs) and explore its possible mechanism.Methods: hPDLSCs were isolated and, then characterized by flow cytometry. Cell-counting kit-8 (CCK-8) and colony assays were used to validate the effect of different NG-R1 concentrations on hPDLSCs proliferation and the optimal concentration was determined. Quantitative detection of alkaline phosphatase (ALP) activity at optimal concentration and the mineralization of the cells was investigated by Alizarin Red S staining. qRT-PCR and Western blot were utilized to examine the factors expression levels of ALP, Runx Family Transcription Factor 2 (RUNX2), Collagen I (Col-1) and catenin beta 1 (CTNNB1; β-catenin). In addition, the tankyrase inhibitor XAV-939 was used to explore NG-R1's role in canonical Wnt signaling.Results: hPDLSCs were positive for surface antigens CD90 while negative for CD34 and CD45, which indicated that we have successfully isolated the hPDLSCs. Furthermore, a concentration of 20μmol NG-R1 dramatically enhanced hPDLSCs proliferation, ALP activity, and mineral deposition. ALP, RUNX2, COL-1, and β-catenin expression were all rised in comparison to control group. After XAV-939 was added to disrupt the canonical Wnt signaling, the impact of NG-R1 appeared to be reversed.Conclusion: These findings suggest that NG-R1 can stimulate osteogenic differentiation of hPDLSCs, which is probably attributable to canonical Wnt signaling activation.Keywords: notoginsenoside R1, NG-R1, human periodontal ligament stem cells, hPDLSCs, osteogenesis, β-catenin